Pengaruh Gaya Kepeimpinan Dan Kompensasi Guna Menaikkankan Kinerja Karyawan Pada CV. Sinar Terang Supermarket Kota Probolinggo - Umi Kulsum; Khusnik Khudzahfidah; Agung Yatiningrum (Universitas Panca Marga, 2023)
This research is to find out how much influence leadership and compensation styles have on employee performance at CV. Bright Light Supermarket Probolinggo City. The type of research used in this study is a type of quantitative research with an associative approach. This study uses Observation, Documentation, Interview, Questionnaire methods using primary data and secondary data obtained from questionnaires and processed data. The sample in this study were 72 employees. The results of this study indicate that leadership style has a dominant influence on employee performance. The results of this study also show that Leadership Style and Compensation have a simultaneous and partial effect on employee performance. CV. Sinar Terang Supermarket Kota Probolinggo pays close attention to Leadership Style and Compensation to be able to improve employee performance, because the better the work given, the company will get good results in the future.